Effectiveness of Inpatient Psychotherapy for Patients With and Without Migratory Background: Do They Benefit Equally? - Kobel, Friederike; Morawa, Eva; Erim, Yesim (Frontiers in Psychiatry, 2020)
Background: Research on the effectiveness of inpatient psychotherapy for migrant patients predominantly concludes that they have greater symptom severity at admission and benefit less from psychotherapy. This study aims to compare symptom severity and effects of psychotherapy regarding depression, somatoform disorders, anxiety disorder, and posttraumatic stress disorder (PTSD) in a sample of patients with and without migratory background (MB). Methods: Symptom severity of 263 patients (T0, pretreatment) and 256 patients (T1, posttreatment) was assessed using the Patient Health Questionnaire-15 somatization module (PHQ-15), depression module (PHQ-9), and general anxiety disorder module (GAD-7), and the PTSD Checklist (PCL-5). Calculations were made for a completer sample and an intention-to-treat (ITT) sample. To investigate the effectiveness of psychotherapy, we calculated effect sizes (Cohen’s d) and clinically significant changes using the reliable change index (RCI). Results: Patients with MB showed significantly higher symptom burden at admission for somatization (p = 0.025, d = 0.345) and posttraumatic symptoms (p = 0.008, d = 0.424) than patients without MB. At discharge, patients with MB reported significantly higher severity regarding all assessed symptoms (somatization: p = 0.001, d = 0.507; depression: p = 0.045, d = 0.313; anxiety: p = 0.012, d = 0.428; traumatization: p = 0.040, d = 0.329) compared with nonmigrant patients. Patients without MB improved significantly regarding all assessed symptoms (somatization: p < 0.001, d = -0.304; depression: p < 0.001, d = -0.692; anxiety: p < 0.001, d = -0.605; posttraumatic symptoms: p < 0.001, d = -0.204). Patients with MB improved significantly concerning depression (p < 0.001, d = -0.649) and anxiety (p = 0.002, d = -0.441). Occurrence of comorbidity was high (87.1% had more than one psychiatric diagnosis). Neurotic, stress-related, and somatoform disorders (F4) and personality disorders (F6) were more frequent among patients with MB. Conclusions: Patients with MB showed higher symptom severity at admission. Our study demonstrated a significant reduction of depressive and anxiety symptoms among patients with MB receiving psychotherapy. Further research is needed to identify interventions that effectively improve somatization and posttraumatic stress for patients with MB, since these symptoms were not significantly reduced.